Patient choice for high‐volume center radiation impacts head and neck cancer outcome. (2nd September 2018) - Naghavi, Arash O.; Echevarria, Michelle I.; Strom, Tobin J.; Abuodeh, Yazan A.; Venkat, Puja S.; Ahmed, Kamran A.; Demetriou, Stephanie; Frakes, Jessica M.; Kim, Youngchul; Kish, Julie A.; Russell, Jeffery S.; Otto, Kristen J.; et al.
Abstract: Background: Studies suggest treatment outcomes may vary between high (HVC)‐ and low‐volume centers (LVC). Radiation therapy (RT) for head and neck cancer (HNC) requires weeks of treatment, the inconvenience of which may influence a patient's choice for treatment location. We hypothesized that receipt of RT for HNC at a HVC would influence outcomes compared to patients evaluated at a HVC, but who chose to receive RT at a LVC. Methods: From 1998 to 2011, 1930 HNC patients were evaluated at a HVC and then treated with RT at either a HVC or LVC. Time‐to‐event outcomes and treatment factors were compared. Results: Median follow‐up was 34 months. RT was delivered at a HVC for 1368 (71%) patients and at a LVC in 562 (29%). Patients were more likely to choose HVC‐RT if they resided in the HVC's county or required definitive RT (all P < 0.001). HVC‐RT was associated with a significant improvement in 3‐year LRC (84% vs 68%), DFS (68% vs 48%), and OS (72% vs 57%) (all P < 0.001). On multivariate analysis (MVA), HVC‐RT independently predicted for improved LRC, DFS, and OS (all P < 0.05). Conclusions: In patients evaluated at a HVC, the choice of RT location was primarily influenced by their residing distance from the HVC. HVC‐RT was associated with improvements in LRC, DFS, and OS in HNC. As treatment planning and delivery are technically demanding in HNC, the choice to undergo treatment at a HVC may result in more optimal delivered dose, RT duration, and outcome. Abstract : Patient choice to undergo radiation therapy at a high‐volume center (HVC) was primarily influenced by their residing distance from the HVC. HVC radiation treatment was associated with improvements in locoregional control, disease‐free survival, and overall survival in head and neck cancer.